Pemberian Stimulus PBB-P2 untuk Mendorong Partisipasi Masyarakat dalam Meningkatkan Pendapatan Daerah di Kabupaten Buleleng - Sumantri, Made Prisma Dewi; Widnyani , Ida Ayu Putu Sri; Astawa , I Wayan (Penerbit Goodwood, 2023)
Purpose: One form of community participation in the context of increasing regional financial independence is through tax collection. Rural and Urban Land and Building Tax (PBB-P2) is one of the taxes that contribute greatly to regional revenue receipts. To analyze and describe why community participation in increasing rural and urban land and building tax revenues in Buleleng Regency has not been optimal, what are the obstacles that cause community participation in increasing rural and urban land and building tax revenues in Buleleng Regency not yet optimal, and how strategies carried out so that community participation in increasing rural and urban land and building tax revenues in Buleleng Regency can be optimal. Research methodology: The research method in this research is descriptive qualitative. The instrument used in this research is an interview guide. Qualitative data analysis techniques, namely data analysis techniques consist of three streams of activity simultaneously, namely data reduction, data presentation, and drawing conclusions. Result: community participation in increasing regional income is not optimal due to the different constraints on the ability to pay each taxpayer, the provision of stimulus is not in accordance with the will of the community because many taxpayers want stimulus to be given for high tax bills, so many people cannot fulfilling their obligations and the lack of rewards given to taxpayers who are aware, obedient in paying taxes and information on tax discounts has not been conveyed properly to the public. The strategy undertaken to optimize community participation in increasing regional income is by conducting a review of the granting of abolition or reduction as well as PBB-P2 rates. Limitations: In this study only used a few informants, therefore future research may consider using more informants. Contribution: This research contributes to the Regional Government of Buleleng Regency.